2019
DOI: 10.1210/jc.2019-00074
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Mitigates Bone Loss in Women With Severe Obesity After Roux-en-Y Gastric Bypass: A Randomized Controlled Trial

Abstract: Context Bone loss after bariatric surgery potentially could be mitigated by exercise. Objective To investigate the role of exercise training (ET) in attenuating bariatric surgery–induced bone loss. Design Randomized, controlled trial. Setting Referral center for bariatric surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
1
18

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(125 citation statements)
references
References 47 publications
1
105
1
18
Order By: Relevance
“…A recent randomized controlled trial evaluated whether bone loss after RYGB could be prevented or decreased by resistance training. Although the study had small patient numbers and a short follow-up of 6 months, the authors showed that compared with RYGB alone (n 5 25), patients undergoing resistance exercise training (n 5 24) were able to mitigate the percent loss of BMD, measured using QCT as the estimated mean difference (EMD) of the femoral neck (EMD, 22.91%; P 5 .007), total hip (EMD, 22.26%; P 5 .009), and distal radius (EMD, 21.87%; P 5 .038), with attenuation of several bone turnover markers [30]. In addition, changes in gut hormones that are produced in fat tissue, such as adipokines, leptin, and adiponectin, are reduced after RYGB, while there are increases in other gut hormones, like PYY, glucagon-like peptide-1, and ghrelin, which has been shown in vitro to increase osteoclastic cell proliferation, although this finding has not been confirmed in patients using BMD and DXA [28,31].…”
Section: Gastric Bypassmentioning
confidence: 99%
“…A recent randomized controlled trial evaluated whether bone loss after RYGB could be prevented or decreased by resistance training. Although the study had small patient numbers and a short follow-up of 6 months, the authors showed that compared with RYGB alone (n 5 25), patients undergoing resistance exercise training (n 5 24) were able to mitigate the percent loss of BMD, measured using QCT as the estimated mean difference (EMD) of the femoral neck (EMD, 22.91%; P 5 .007), total hip (EMD, 22.26%; P 5 .009), and distal radius (EMD, 21.87%; P 5 .038), with attenuation of several bone turnover markers [30]. In addition, changes in gut hormones that are produced in fat tissue, such as adipokines, leptin, and adiponectin, are reduced after RYGB, while there are increases in other gut hormones, like PYY, glucagon-like peptide-1, and ghrelin, which has been shown in vitro to increase osteoclastic cell proliferation, although this finding has not been confirmed in patients using BMD and DXA [28,31].…”
Section: Gastric Bypassmentioning
confidence: 99%
“…Weight-bearing exercise increases bone density 7 , so pressure from excessive weight may strengthen bone 8 . Consistent with this, significant weight loss achieved with bariatric surgery results in bone loss 9 , which can be mitigated by exercise 10 . However, despite more bone mass, obesity confers an increased risk of osteoporosis 11 and bone fractures 12 , at least in some sites.…”
Section: How Does Obesity Influence Bone?mentioning
confidence: 59%
“…Several studies have suggested that supervised exercise programs can partially mitigate bone loss after RYGB. ( 49,50 ) It remains unknown whether other bone‐modifying treatments can fully prevent RYGB‐induced high‐turnover bone loss.…”
Section: Discussionmentioning
confidence: 99%